Creative Drama-Based Psychoeducation: The Effect on Improving Emotional Intelligence of Adolescent Orphans - Makruf, Herlin Asfarina; Sudirman, Dhiya Fauziyyah; Fasikhah, Siti Suminarti (Psympathic : Jurnal Ilmiah Psikologi, 2025)
This study aimed to analyze the effect of creative drama-based psychoeducation on emotional intelligence in adolescents. A one-group pretest and posttest quasi-experimental design was adopted. Before the treatment, an initial assessment was conducted, and 10 adolescents from an orphanage were assigned. Creative drama-based psychoeducation consisted of five sessions. Three assessments were conducted, namely emotional intelligence scale, general knowledge related to emotional intelligence, knowledge related to emotional intelligence skills. The results showed that creative drama-based psychoeducation had a significant effect on emotional intelligence of adolescents in orphanage with a significance value of .005 (p value <.05). Based on this result, analysts, practitioners, and parties were expected to cooperate and play an active role in developing emotional intelligence of adolescents in orphanage through creative drama-based psychoeducation.